No melhor interesse da criança? a ênfase na adoção como garantia do direito à convivência familiar e comunitária - Oliveira, Rita de Cassia Silva (2015)
In light of the theoretical and ethical-political foundations of Social Work, this thesis discusses the right to family and community life and the recurrent decision of the government and civil society to prioritize adoption as a way to "solve" the situation of children and adolescents living in institutions. Between 2003 and 2009, we experienced a clash between antagonistic postures in defense of this right, which occurred together with the dissemination of researches on childcare that highlighted the need for the State to implement more effective policies to ensure the exceptionality and temporality of this protection measure. As participants in the São Paulo movement against the approval of the National Adoption Bill No. 1756-2003, we aim to contribute to the understanding of the processuality which resulted in the enactment of the law No. 12.010 in 2009. The text covers the subaltern classes historic rupture legacy of family life and community, claiming back, in legislation, the genesis of the ideas of adoption as a "solution" for those who are taken in. The approach to the course of the the National Adoption Bill No. 1756-2003 sought to answer the following guiding questions: What is the concept of family and community life that permeated the debates? How was the articulation of the PNCFC construction process and the legal procedures of PLNA? What is the influence of the São Paulo movement, contrary to the PL, on its legal procedures in the legislative process? What remained from the original proposals and what has substantially changed? Are there new bills pending whose purpose is to make adopting agile? And after all, was the centrality of the family strengthened in terms of support or accountability in a familist perspective? In order to be able to reconstruct all this, we favored the documentary research in primary and secondary sources, such as previous versions of the plan and several bills in addition to the National Adoption Bill No. 1756-2003, as well as the results of public consultations and shorthand transcripts of sessions of the House of Representatives. The conclusion shows that, in the gap between the legal guarantee and the reality of no access to fundamental rights, the "centrality of the family" can assume perspectives that reinforce the process of inequality they experience. Despite the legal and regulatory advances, actions in defense of the fundamental right to family and community life tended to emphasize the reorganization of institutional care services, the need for the implementation of foster care and the adoption-centered interests of the child, having progressed very little in terms of the control of public policies aiming at the protection of socialization, prevention of rupture and reintegration to the family of origin. Anchored in a contradiction of the Brazilian capitalist society - economic reordering overlaps the social investment, which focuses on meeting the minimum necessary needs - public actions still tend to reproduce failing mechanisms of rupture instead of mechanisms of promotion and strengthening of the family and community life of subaltern classes in the child best interest